The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/2016gl072408
|View full text |Cite
|
Sign up to set email alerts
|

Tropical ocean‐atmospheric forcing of Late Glacial and Holocene glacier fluctuations in the Cordillera Blanca, Peru

Abstract: Evaluating the timing and style of past glacier fluctuations in the tropical Andes is important for our scientific understanding of global environmental change. Terrestrial cosmogenic nuclide ages on moraine boulders combined with 14C‐dated clastic sediment records from alpine lakes document glacial variability in the Cordillera Blanca of Peru during the last ~16 ka. Late Glacial ice extents culminated at the start of the Antarctic Cold Reversal and began retracting prior to the Younger Dryas. Multiple moraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The Late Glacial TCN ages from Queshque (Stansell et al, 2017) are comparable to the Glasser et al (2009) and Smith and Rodbell (2010) Late Glacial and Holocene TCN ages from the nearby Jeullesh valley. The available The M5 moraine (15.7 ± 1.8 ka) has been interpreted by Smith and Rodbell (2010) as recessional, or possibly a stillstand feature.…”
Section: Cordillera Blancasupporting
confidence: 67%
See 1 more Smart Citation
“…The Late Glacial TCN ages from Queshque (Stansell et al, 2017) are comparable to the Glasser et al (2009) and Smith and Rodbell (2010) Late Glacial and Holocene TCN ages from the nearby Jeullesh valley. The available The M5 moraine (15.7 ± 1.8 ka) has been interpreted by Smith and Rodbell (2010) as recessional, or possibly a stillstand feature.…”
Section: Cordillera Blancasupporting
confidence: 67%
“…Evidence for early Holocene readvances or stillstands in the Cordillera Blanca is recorded in TCN ages and supported by the lake sediment data from the Queshque valley (Stansell et al, 2017). End moraines enclosing Upper Queshquecocha were constructed ca.…”
Section: Cordillera Blancamentioning
confidence: 83%
“…Some studies have associated dated moraines with the YD (Glasser et al, 2009;Rodbell et al, 2009;Zech et al, 2010;Kelly et al, 2012;Martini et al, 2017), but this correlation can be difficult to demonstrate unambiguously when calculated ages have uncertainties of ~1 ka and the YD interval only lasted from 12.9 ka to 11.7 ka (Bromley et al, 2011;Ward et al, 2015). Jomelli et al (2014) suggested that moraine ages may instead correlate with the slightly earlier Antarctic Cold Reversal (ACR; 14.7-13.0 ka), as supported by high-precision dating of a moraine system in Colombia (Jomelli et al, 2014), a compilation of revised ages across the Central Andes (Jomelli et al, 2017), and some additional moraine chronologies from individual locations (e.g., Stansell et al, 2017). The ACR was an abrupt cooling event in the Southern Hemisphere that pre-dated the YD, coinciding with the Bølling-Allerød interstadial in the Northern Hemisphere (Blunier et al, 1997).…”
Section: Modern and Past Climatementioning
confidence: 99%
“…For the reasons outlined in Section 3.1, many studies take the oldest boulder age-within a cluster of boulder ages for a given moraine and after the exclusion of outliers attributed to nuclide inheritance-to be the closest to the timing of the glacier advance (e.g., Zech et al, 2006Zech et al, , 2007aZech et al, ,b, 2009bZech et al, , 2010Hall et al, 2009;May et al, 2011). On the contrary, some studies instead (i) calculate mean values of all boulder ages collected on a moraine (Licciardi et al, 2009;Shakun et al, 2015b;Stansell et al, 2015Stansell et al, , 2017Bromley et al, 2016;Martini et al, 2017); (ii) calculate average boulder ages using frequency density plots (Smith and Rodbell, 2010;Jomelli et al, 2011;Smith et al, 2011;Ward et al, 2015); (iii) organise ages chronologically and take the plateau or modal age (Smith et al, 2005a,b) or (iv) combine these various approaches . As our results for the Sierra de Aconquija demonstrate (see Section 4.1), these different approaches could, in some cases, result in substantially different moraine ages (and consequently palaeoclimate interpretations) for an identical set of boulder ages.…”
Section: Andesmentioning
confidence: 99%
See 1 more Smart Citation